PENGARUH FINANCIAL DISTRESS DAN REPUTASI AUDITOR TERHADAP OPINI AUDIT GOING CONCERN DENGAN KOMITE AUDIT SEBAGAI PEMODERASI - Iriyanti Iriyanti; M. Hendri Yan Nyale (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Going Concern Audit Opinion can predict whether or not a company may go bankrupt, including one component of a going concern decision. Several factors related to the Going Concern Audit Opinion in this study are the influence of financial distress and the reputation of the auditors and the audit committee as moderators. The purpose of this study was to study and analyze the effect of financial distress and auditor reputation on the provision of going concern audit opinions with the existence of an audit committee as moderating agent for property and real estate companies listed on the Indonesia Stock Exchange (IDX) 2015-2019. The sample taken in this study used purposive sampling. Data analysis using logistic analysis method. The results showed that financial distress and auditor reputation variables had partial or simultaneous influence on going concern audit opinion and the existence of an audit committee was not able to moderate the relationship between financial distress and auditor reputation on going concern audit opinion